1991
DOI: 10.1055/s-2007-1003765
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated Response of Thyrotropin and Prolactin to Dopamine Receptor Blockade with Domperidone in Hypothyroid Subjects

Abstract: To investigate the hypothesis of an altered hypothalamic dopaminergic activity in primary hypothyroidism, eight patients with hypothyroidism and seven normal subjects, all female, were studied. All of them were submitted to two tests: TRH stimulation and after the administration of dopamine receptor-blocking drug, Domperidone. The hypothyroid patients with basal TSH values less than or equal to 60 mU/L (4 cases--group 1) had lower PRL levels than the remaining 4 subjects with TSH greater than 60 mU/L (group 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Although the underlying mechanism is unclear, a few hypotheses have been off ered to explain how a hypothyroid state might induce a manic episode. One hypothesis is that hypothyroidism causes an increase in cerebral dopamine along with an increase in tyrosine hydroxylase activity [6,18,19] . Goodwin & Sachs suggested that excess of monoamines, especially dopamine, results in manic symptoms [20] .…”
Section: Case Report 3 ▼mentioning
confidence: 99%
“…Although the underlying mechanism is unclear, a few hypotheses have been off ered to explain how a hypothyroid state might induce a manic episode. One hypothesis is that hypothyroidism causes an increase in cerebral dopamine along with an increase in tyrosine hydroxylase activity [6,18,19] . Goodwin & Sachs suggested that excess of monoamines, especially dopamine, results in manic symptoms [20] .…”
Section: Case Report 3 ▼mentioning
confidence: 99%